Syi’ah dan Tafsir al-Mīzān fī Tafsīr al-Qur’ān karya Muḥammad Ḥusein al-Ṭabātabā’ī - Anshori Anshori (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This paper examines the interpretation of Muhammad Husein al-Tabataba’i on QS. al-Zumar (39): 65 and QS. al-Baqarah (2): 136 in his commentary, al-Mizan fi Tafsir al-Qur’an. This study aims to show that there is a side of moderation in the interpretation of al-Ṭabataba'i which leads to the Sunni meaning, in this case, the interpretation of monotheism. The research method used in this study is descriptive analysis, which is to collect related data and then analyze it. The data analysis used refers to what is offered by Huberman & Miles, namely, data reduction, data presentation, and conclusions or verification. The results of this study indicate that the interpretation of al-Ṭabataba'i on QS. al-Zumar (39): 65 and QS. al-Baqarah (2): 136 is different from the interpretation of the Shiites, in this case, the interpretation of al-Kulaini. Al-Ṭabataba'i interprets the word shirk in QS. al-Zumar (39): 65 by associating partners with Allah as is the case with the Sunnis, not associating partners with the Imams, as interpreted by al-Kulaini. Then also interpret the word of God